2020
DOI: 10.20527/k.v9i2.8824
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Plastic Waste for Making Brickets: The Effect of Composition on Procsimate Analysis

Abstract: Penanganan untuk mengurangi dan pemanfaatan limbah plastik masih belum optimal. Volume limbah plastik terus bertambah seiring bertambahnya jumlah penduduk. Limbah plastik merupakan sumber pencemaran lingkungan yang sulit terdegradasi. Tujuan dari penelitian ini adalah mengkaji pengaruh komposisi arang limbah plastik sebagai bahan baku briket terhadap analisa proksimat. Limbah plastik yang digunakan adalah tutup botol dan kemasan makanan ringan. Pirolisis dilakukan pada suhu 450oC untuk tutup botol dan 280oC un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Optimal conditions plastic percent at 24% and 20% adhesive percent. Ningsih and Udyani (2020) reported that charcoal briquettes from plastic bottle waste is in accordance with SNI were under conditions of 40 mesh charcoal particle size, with a water content of 0.5±0.05%, an ash content of 2±0 .25%, volatile content of 15±0.51%, bound carbon content of 82.5±0.32%, and calorific value of 9982.779±240.017 cal/gram.…”
Section: Gasification Processmentioning
confidence: 85%
See 2 more Smart Citations
“…Optimal conditions plastic percent at 24% and 20% adhesive percent. Ningsih and Udyani (2020) reported that charcoal briquettes from plastic bottle waste is in accordance with SNI were under conditions of 40 mesh charcoal particle size, with a water content of 0.5±0.05%, an ash content of 2±0 .25%, volatile content of 15±0.51%, bound carbon content of 82.5±0.32%, and calorific value of 9982.779±240.017 cal/gram.…”
Section: Gasification Processmentioning
confidence: 85%
“…Briquettes are the result of converting coal, organic waste, factory waste and from urban waste into fuel that is more effective, efficient and easy to use (Sawir, 2016). The briquettes produced are then analyzed for the quality of the briquettes using the proximate analysis (Ningsih, 2020).…”
Section: Briquettementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the utilization of plastic waste to produce biobriquettes has resulted in a calorific value of 8565.914 cal/g, a moisture content of 5.47%, and an ash content of 4.95%. These biobriquettes meet Indonesian national standards (Ningsih & Udyani, 2020). Additionally, biobriquettes made from corn cobs have been successfully characterized with a calorific value of 5666 cal/g, moisture content and ash content at 3.67% and 4.83%, respectively.…”
Section: Introductionmentioning
confidence: 87%
“…The materials were then dried at 105ºC for 24 h in an oven. This process was conducted to eliminate moisture content thus preventing rotting [3]. The analysis of lignocellulose content, proximate and calorific value of the raw material was conducted.…”
Section: Pre-treatment Of Raw Materialsmentioning
confidence: 99%